Features of the impact of the COVID-19 pandemic on the prevalence of certain respiratory diseases of infections etiology - I. A. Sorokin; M. V. Nikolskaya; V. L. Melnikov (Сибирский научный медицинский журнал, 2024)
The aim of the study was to assess the impact of the COVID-19 pandemic on the incidence of respiratory infections of the population of Penza region in different age groups. Material and methods. The analysis of statistical reporting data (Form 12) on the number of diseases in the service area of the medical organization in Penza region was carried out. Information was sampled on respiratory diseases of infectious etiology for the period from 2015 to 2022 and on COVID-19 morbidity in the period from 2020 to 2022 among patients of different age periods. The data is presented as a calculation per 100 thousand population. Results. In 2020, compared to 2019, there was a pronounced increase in the number of respiratory diseases (p = 0.000) in adults; in 2021, the incidence decreased slightly, being higher until 2022 than in the period before the pandemic (p = 0.000). Among children and adults, there was an increase in the incidence of acute respiratory infections in 2022 compared to 2015 (p < 0.001). Peak incidence of croup and epiglottitis among children and adolescents was observed in 2020. The incidence of COVID-19 among adolescents (8339.6) and adults (7678.5) was significantly higher than the incidence among children (5949.9) (p = 0.000). Discussion. Respiratory diseases of infectious etiology have an acute course, so primary morbidity predominates. In adults, the proportion of primary morbidity is decreasing, which may be related to an increase in chronic diseases of the respiratory system. The weak impact of the pandemic on pediatric respiratory diseases incidence is supported by the low pediatric incidence of COVID-19. The increased incidence of COVID-19 among adolescents is alarming; it supports the assumption that child and young adult populations have proven to be major gateways for the spread of COVID-19 to adults. The high incidence of croup and epiglottitis in 2020 among children (p = 0.024) and adolescents could be one of the symptoms of COVID-19 characteristic of younger age. Conclusions. COVID-19 had no effect on the increase in respiratory disease among children, but children contributed to the spread of infection among adults. There is a trend towards an increase in chronic respiratory disease in adults. RBD of infectious etiology is almost impossible to predict, except for acute laryngitis and tracheitis among adults. In adolescents and children against the background of COVID-19 infection, a large number of more severe symptoms may appear.